Robust Cardinality and Cost Estimation for Skyline Operator - Chaudhuri, Surajit; Dalvi, Nilesh; Kaushik, Raghav (ICDE, 2006)
Incorporating the skyline operator inside the relational engine requires solving the cardinality estimation and the cost estimation problem, hitherto unaddressed. We propose robust techniques to estimate the cardinality and the computational cost of Skyline, and through an empirical comparison, show that our technique is substantially more effective than traditional approaches. Finally, we show through an implementation in Microsoft SQL Server that skyline queries can substantially benefit from our techniques